Anisotropic satellite galaxy quenching modulated by black hole activity - Martín-Navarro, Ignacio; Pillepich, Annalisa; Nelson, Dylan; Rodriguez-Gomez, Vicente; Donnari, Martina; Hernquist, Lars; Springel, Volker (Nature, 2021)
The evolution of satellite galaxies is shaped by their constant interaction with the circumgalactic medium surrounding central galaxies, which in turn may be affected by gas and energy ejected from the central supermassive black hole1-6. The nature of such a coupling between black holes and galaxies is, however, much debated7-9 and observational evidence remains scarce10,11. Here we report an analysis of archival data on 124,163 satellite galaxies in the potential wells of 29,631 dark matter halos with masses between 1012 and 1014 solar masses. We find that quenched satellite galaxies are relatively less frequent along the minor axis of their central galaxies. This observation might appear counterintuitive given that black hole activity is expected to eject mass and energy preferentially in the direction of the minor axis of the host galaxy. We show, however, that the observed anisotropic signal results precisely from the ejective nature of black hole feedback in massive halos, as outflows powered by active galactic nuclei clear out the circumgalactic medium, reducing the ram pressure and thus preserving star formation in satellite galaxies. This interpretation is supported by the IllustrisTNG suite of cosmological numerical simulations, even though the model’s sub-grid implementation of black hole feedback is effectively isotropic12.